POTENSI DAN STRATEGI OPTIMALISASITERHADAP AKTIVITASPETANI GARAMMELALUIPENDEKATAN HULU HILIR DI KAWASAN PESISIRPENAMBANGAN KECAMATAN PAJARAKANKABUPATEN PROBOLINGGO - Mustofa Mustofa; Rafael Purtomo Sumaji; Siti Komariyah (RELASI : JURNAL EKONOMI, 2014)
Potential and optimization strategies to salt farmer activities conducted by the characteristics of the potential of aregion. Northern waters of Java representsacondition characteristic of coastal resources whichrequire specific management. Coastal resource potential Penambangan are extremely large, but growing salt farmer activities have not been able to change the level of welfare in the coastal zona Penambangan. This study aims to:1) identify the potential diversity of economic activities of salt farmer communities in the Coastal Zone Penambangan, 2) find out some strategies and optimization of economic activity in the salt farmer communities of Coastal Zone District Penambangan Pajarakan Probolinggo and 3) examine the economicactivity from upstream to downstream coastal areas in District Pajarakan ProbolinggoThis study uses a form of qualitative research is conducted on an object and condition as it is. The data was collected by way of gathering information or data about the use of natural resources by coastal salt farmer from upstream to downstream in the coastal zone district Penambangan Pajarakan Probolinggo. These results indicate that the coastal areas of economic activity penambangan current caused by the presence of salt farmer activities as salt business activity in the system. The series is linked salt farmer linkages (backward and forward) which took place on the upstream and downstream activities that give rise tomultiplier effects of employment and income gains value. Salt value chain linkages implies that the growthof entrepreneurship can openup employment opportunities for local communities (local) that is based on the utilization of coastal marine resources (natural, human, institutional and capital). The types of businesses that are involved in fishing activities in the area include Penambangan;pre-production stages, the stages of production and post production stages.